2004
DOI: 10.1002/j.1939-4640.2004.tb03170.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Glucocorticoid Mediation of Suppressed Testosterone Biosynthesis in Male Mice Subjected to Immobilization Stress

Abstract: Physical and psychosocial stress challenge homeostasis, increasing glucocorticoid secretion (in rodents, corticosterone [CORT]) while decreasing testosterone (T) levels. The dynamics of stress-induced changes in T, CORT, and luteinizing hormone (LH) concentrations in mice have not been investigated previously. In particular, it remains to be established whether there is a rapid effect of CORT that is directly mediated by glucocorticoid receptors (GRs) in the testis. Therefore, serum and intratesticular T, seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
70
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(81 citation statements)
references
References 65 publications
8
70
0
3
Order By: Relevance
“…The decrese in testosterone likely reflects the increase in corticosterone during chronic stress. This may be mediated by non-genomic mechanisms [Dong et al 2004] or genetic mechanisms through the inhibition of genes encoding testosterone biosynthetic enzymes [Payne and Sha 1991], such as 3b-hydroxysteroid dehydrogenase and 17a-hydroxylase/17-20-lyase [Hales and Payne 1989;Orr et al 1994]. Corticosterone also induces Leydig cell apoptosis [Chen et al 2012], resulting in a significant reduction in the secretion of testosterone [Hardy et al 2005] as confirmed by TUNEL.…”
Section: Discussionmentioning
confidence: 99%
“…The decrese in testosterone likely reflects the increase in corticosterone during chronic stress. This may be mediated by non-genomic mechanisms [Dong et al 2004] or genetic mechanisms through the inhibition of genes encoding testosterone biosynthetic enzymes [Payne and Sha 1991], such as 3b-hydroxysteroid dehydrogenase and 17a-hydroxylase/17-20-lyase [Hales and Payne 1989;Orr et al 1994]. Corticosterone also induces Leydig cell apoptosis [Chen et al 2012], resulting in a significant reduction in the secretion of testosterone [Hardy et al 2005] as confirmed by TUNEL.…”
Section: Discussionmentioning
confidence: 99%
“…Leydig cells were isolated as described in ref. 41. Brief ly, testes from adult mice were decapsulated and dispersed in a shaking water bath at 34°C for 10 min in 10 ml of Medium 199 (M-199) with 0.25 mg/ml collagenase D, 35 mU/ml Dispase II, and 6 g/ml DNase I.…”
Section: Methodsmentioning
confidence: 99%
“…A rapid action of glucocorticoids on Leydig cell function was also demonstrated. A rapid (30-min) decline of testosterone production was seen in mouse Leydig cells when these cells were exposed to 1.44 µM corticosterone (CORT), indicating that a non-genomic mechanism of glucocorticoids in Leydig cells [28], since the genomic mechanism of glucocorticoids requires hours to register at the protein level [29]. CORT can inhibit cAMP formation in mouse Leydig cells within 15 min [28].…”
Section: Rapid Glucocorticoid Actions Via Membrane Receptorsmentioning
confidence: 99%